Experimental and Theoretical Study of Stable and Metastable Phases in Sputtered CuInS2 - Jes K. Larsen; Kostiantyn V. Sopiha; Clas Persson; Charlotte Platzer‐Björkman; Marika Edoff (Advanced Science, 2022)
Abstract The chalcopyrite Cu(In,Ga)S2 has gained renewed interest in recent years due to the potential application in tandem solar cells. In this contribution, a combined theoretical and experimental approach is applied to investigate stable and metastable phases forming in CuInS2 (CIS) thin films. Ab initio calculations are performed to obtain formation energies, X‐ray diffraction (XRD) patterns, and Raman spectra of CIS polytypes and related compounds. Multiple CIS structures with zinc‐blende and wurtzite‐derived lattices are identified and their XRD/Raman patterns are shown to contain overlapping features, which could lead to misidentification. Thin films with compositions from Cu‐rich to Cu‐poor are synthesized via a two‐step approach based on sputtering from binary targets followed by high‐temperature sulfurization. It is discovered that several CIS polymorphs are formed when growing the material with this approach. In the Cu‐poor material, wurtzite CIS is observed for the first time in sputtered thin films along with chalcopyrite CIS and CuAu‐ordered CIS. Once the wurtzite CIS phase has formed, it is difficult to convert into the stable chalcopyrite polymorph. CuIn5S8 and NaInS2 accommodating In‐excess are found alongside the CIS polymorphs. It is argued that the metastable polymorphs are stabilized by off‐stoichiometry of the precursors, hence tight composition control is required.